The Advancement of Targeted Alpha Therapy and the Role of Click Chemistry Therein - Sara Lacerda; Robin M. de Kruijff; Kristina Djanashvili (Molecules)
Recent years have seen a swift rise in the use of α-emitting radionuclides such as 225Ac and 223Ra as various radiopharmaceuticals to treat (micro)metastasized tumors. They have shown remarkable effectiveness in clinical practice owing to the highly cytotoxic α-particles that are emitted, which have a very short range in tissue, causing mainly double-stranded DNA breaks. However, it is essential that both chelation and targeting strategies are optimized for their successful translation to clinical application, as α-emitting radionuclides have distinctly different features compared to β−-emitters, including their much larger atomic radius. Furthermore, upon α-decay, any daughter nuclide irrevocably breaks free from the targeting molecule, known as the recoil effect, dictating the need for faster targeting to prevent healthy tissue toxicity. In this review we provide a brief overview of the current status of targeted α-therapy and highlight innovations in α-emitter-based chelator design, focusing on the role of click chemistry to allow for fast complexation to biomolecules at mild labeling conditions. Finally, an outlook is provided on different targeting strategies and the role that pre-targeting can play in targeted alpha therapy.